2010
DOI: 10.4049/jimmunol.1002165
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Caspase-1 Activation via NLRP3/NLRC4 Inflammasomes Mediated by Aerolysin and Type III Secretion System during Aeromonas veronii Infection

Abstract: Aeromonas spp. are Gram-negative bacteria that cause serious infectious disease in humans. Such bacteria have been shown to induce apoptosis in infected macrophages, yet the host responses triggered by macrophage death are largely unknown. In this study, we demonstrate that the infection of mouse bone marrow-derived macrophages with Aeromonas veronii biotype sobria triggers activation of caspase-1 with the ensuing release of IL-1β and pyroptosis. Caspase-1 activation in response to A. veronii infection require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 40 publications
2
55
0
1
Order By: Relevance
“…5B and C), suggesting that the presence of LPS in the bloodstream, which may occur after structural or functional damage to the colon associated with S. dysenteriae serotype 1 or STEC infections, augments proinflammatory cytokine production, leading to increased localized vascular damage. Among numerous inflammasome activators, the NLRP3 inflammasome is strongly activated by a large number of bacterial toxins (63)(64)(65)(66). One important conceptual question that remains to be addressed is whether receptor-mediated internalization of Stxs or the retrotranslocation of functional StxA1 fragments across the ER membrane could be recognized by cytosolic receptors such as NLR inflammasome sensors.…”
Section: Discussionmentioning
confidence: 99%
“…5B and C), suggesting that the presence of LPS in the bloodstream, which may occur after structural or functional damage to the colon associated with S. dysenteriae serotype 1 or STEC infections, augments proinflammatory cytokine production, leading to increased localized vascular damage. Among numerous inflammasome activators, the NLRP3 inflammasome is strongly activated by a large number of bacterial toxins (63)(64)(65)(66). One important conceptual question that remains to be addressed is whether receptor-mediated internalization of Stxs or the retrotranslocation of functional StxA1 fragments across the ER membrane could be recognized by cytosolic receptors such as NLR inflammasome sensors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to viral models, other infectious agents have been associated with NLRP3 inflammasome activation, including immunopathogenesis mechanisms, such as Aeromonas spp. [51] and Borrelia spp. [52] that induce the expression of IL-1β and IL-18, altering the development of inflammatory immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial infection often activates multiple types of inflammasomes, which may play redundant or additive roles in host defense (34,(42)(43)(44)(61)(62)(63)(64)(65). Using THP-1 cell lines with stable knockdowns of NLRP3 and ASC, we demonstrated that the NLRP3/ASC inflammasome was responsible for H. ducreyi-induced IL-1␤ production.…”
Section: Discussionmentioning
confidence: 96%